Must We Deploy Drones in the Twenty-First Century to Target Under the Radar Discrimination Against Minority Women At Law Schools At Historically Black Colleges and Universities (HBCUs)? - Wu, Edieth Y.; Wu, Edieth Y. (Columbia Journal of Gender and Law, 2015)
This Article is a result of the authors’ participation in the Association of American Law School’s Crosscutting Program (“The More Things Change . . . : Exploring Solutions to Persisting Discrimination in Legal Academia”) at the Annual Meeting in Washington, D.C., in January 2015. … After the Introduction, Part I offers an overview of the history/evolutions of HBCUs. Part II analyzes analogous systems, which operate similarly to and influence historically black colleges and universities. Part III develops the concept of women pretexting authority (“WPA”). Part IV discusses legitimate processes and mechanisms to address infractions at HBCUs after female faculty complain. Part V proposes recommendations to address the persisting problem, until a conclusion is finally reached in Part VI based on the arguments set forth in the analysis.